Identifikasi Tingkat Kecenderungan Perilaku Adiktif Mahasiswa Generasi Z - Erwita Ika Violina; Rafael Lisinus Ginting; Fadinda Aisyah; Salsabila Nasution (Universitas Negeri Medan, 2025)
In today's digital era, the tendency of addiction to technology, social media, and certain substances is increasing, which has the potential to harm the well-being of students. This study aims to identify the level of addictive behavior tendencies in students at Medan city, focusing on two main factors: individual predisposition and specific areas of addiction. Through a descriptive quantitative approach, data were collected from 491 students using a questionnaire that measured addictive tendencies based on various variables, including learning patterns, emotional regulation, impulsivity, and addictive behaviors related to technology, drugs, gambling, and pornography. The results showed that Internet & Technology was the domain with the highest addiction tendencies (M = 17.44), followed by emotional regulation (M = 15.86). Although addiction to Cigarettes, Alcohol, and Drugs showed the lowest mean value (M = 9.53), the high kurtosis value indicates the presence of a group of students with very high addiction. On the other hand, psychological factors such as Impulsivity and low Executive Function contribute to impulsive decision-making that exacerbates addictive behavior. This study recommends the development of more holistic prevention and intervention programs, including enhanced guidance and counseling services and effective coping skills training, to help college students overcome addictive behaviors and improve their psychological well-being.